Factors Influencing Mobile Assisted English Learning Among Malaysian Undergraduates: The Mediating Role Of Self Regulated Learning - Morat, Berlian Nur (2022)
The widespread ownership and use of mobile devices among Malaysian undergraduates is expected to enable them to self-direct their English learning, which is in line with the government’s aspiration to produce autonomous English learners. However, the motivations behind their mobile assisted English learning (MAEL) are unclear due to limited studies in this area. Thus, addressing the gap, this study integrated the Unified Theory of Acceptance and Use of Technology (UTAUT) and Social Cognitive Theory (SCT) to investigate the factors that influence such MAEL behaviour. More specifically, through the integrated theoretical framework, the internal factors (i.e., performance expectancy, effort expectancy, and mobile self-efficacy) and external factors (i.e., social influence and facilitating resources) were proposed to influence Malaysian undergraduates’ MAEL use decisions through the mediating effect of self-regulated learning (SRL). Data were collected by employing a cross-sectional survey using an online Google-based questionnaire in which a number of 400 Malaysian ESL undergraduates identified to practise MAEL were purposively sampled from five public universities in Malaysia.